Improving policy environments for infants and young children: global status of multisectoral national policies for early childhood development. Issue 3 (3rd July 2022) - Vargas-Barón, Emily; Diehl, Kristel; Small, Jason W.
ABSTRACT: Multisectoral national policies for early childhood development (ECD) have been developed since 1979, yet until now the number of countries adopting them has not been systematically documented. Numerous global declarations, including Education for All and the Sustainable Development Goals (SDGs), have supported ECD policy planning. Selection and search criteria were established and applied to identify and classify multisectoral ECD policy documents. A descriptive study was conducted to assess historical trends in policy adoption, regional coverage, income levels, governance categories, and crisis countries. Policies were first developed in Colombia, and later in Namibia, South Africa, Mauritius and Maldives. By December 2019, 76 countries (39% of 197 countries worldwide) and one territory had adopted 125 multisectoral ECD policy instruments. Of them, 51% were policies; 37% strategies and/or action plans; 11% laws; and 7% regulatory documents. By 2010, 43 countries had adopted an ECD policy instrument, peaking in 2011 when 14 countries adopted policies. From 2012 to 2019, 29 countries adopted a policy. South Asia (88%), Latin America and the Caribbean (65%), and Sub-Saharan Africa (58%) lead policy development. Policies have been adopted by 53% of low-income countries and 55% of lower middle-income countries. Fewer upper middle-income countries (38%) and high-income countries (14%) have adopted an ECD policy. Previous research found that countries using participatory policy planning processes resulted in well-implemented ECD policies. The presence of a multisectoral ECD policy prepared in a participatory manner helps establish a strong enabling environment for expanding and improving ECD services. To attain SDG 4.2, additional lower- and middle-income countries, countries with emergencies, and authoritarian regimes should be prioritized for support. Finally, we recommend an indicator be established to identify the number of countries that have adopted ECD policies to help measure SDG 4.2. Key messages: This study provides, for the first time, a criteria-based list of multisectoral national policies for early childhood development (ECD) in 76 countries (39% of 197 countries worldwide) and one territory and examines regional policy coverage and needs. Initial studies reveal the development, adoption, and implementation of multisectoral national ECD policies help expand ECD programs in countries. More technical assistance is needed to develop and implement ECD policies, especially in lower- and middle-income countries, including those with humanitarian emergencies and authoritarian regimes. A new SDG indicator for multisectoral national ECD policy development is recommended for future use. More research is required regarding policy impacts in relation to methods and processes of policy development, structures, key elements, and contents.